CRITERIA FOR ASSESSING STRUCTURAL CHANGES IN THE MYOCARDIUM IN EXPERIMENTAL HYPODYNAMIC AND DIABETES - Odilbek Matkarimov; Sayyora Axmedova; Norbek Niyozov (Central Asian Journal of Medicine, 2025)
The study is devoted to morphological changes in the myocardium under conditions of hypodynamia and diabetes mellitus, which are currently an urgent problem. The study examined heart tissue from 120 rats exposed to hypodynamia and diabetes mellitus and their offspring. The results showed that dystrophic changes are observed in the heart walls of rats under conditions of diabetes mellitus. The maximum level of the inflammatory process was noted in our observations. During this period, perivascular hemorrhages, interstitial edema, lymphohistiocytic infiltration, as well as signs of mucoid and fibrinoid thickening in the myocardial stroma, are observed. Inflammatory processes are more pronounced in the subendocardial area, and an increase in edema is detected.